Application of a three-dimensional printed pelvic model in laparoscopic radical resection of rectal cancer - Lu, Feng; Qiu, Lei; Yu, Peng; Xu, Da-Lai; Miao, Yong-Chang; Wang, Gang (Frontiers in Oncology, 2023)
Introduction To investigate the application value of a three-dimensional (3D) printed pelvic model in laparoscopic radical resection of rectal cancer. Methods Clinical data of patients undergoing laparoscopic radical rectal cancer surgery in The Second People's Hospital of Lianyungang City from May 2020 to April 2022 were selected. Patients were randomly divided into general imaging examination group (control group, n=25) and 3D printing group (observation group, n=25) by random number table method, and the perioperative situation of patients in the two groups was compared. Results There was no significant difference in general data between the two groups (p>0.05). Operation time, intraoperative blood loss, intraoperative time to locate inferior mesenteric artery, intraoperative time to locate left colic artery, first postoperative exhaust time and length of hospital stay in the observation group were all lower than those in the control group (P < 0.05); There were no significant differences in the total number of lymph nodes and complications between the two groups (P > 0.05). Discussion The application of 3D printed pelvic model in laparoscopic radical resection of rectal cancer is conducive to understanding pelvic structure and mesenteric vascular anatomy, reducing intraoperative bleeding and shortening operation time, which is worthy of further clinical application.